Cyber Muslims: mapping Islamic digital media in the internet age - Rozehnal, Robert Thomas (Bloomsbury Academic, 2022)
"Providing detailed case studies, this book explores the vibrant digital expressions of diverse groups of Muslim cybernauts: religious clerics and Sufi mystics, feminists and fashionistas, artists and activists, Hajj pilgrims and celebrities. Together, these stories span a vast cultural and geographic landscape, including Indonesia, Iran, the Middle East, and the United States. These case studies are contextualized within the backdrop of broader social trends, including racism and Islamophobia, gender dynamics, celebrity culture, identity politics, and the shifting dynamics of contemporary religious piety and practice. Authors examine a wide-range of digital multimedia technologies as primary "'texts." These include websites, podcasts, Twitter, Facebook, Instagram, YouTube channels, online magazines and discussion forums, and religious apps. The book's contributors draw on the methodological and theoretical models of multiple academic disciplines, including Religious Studies, Cultural Anthropology, Global Studies, Communication and Media Studies, Religious Studies, and Islamic Studies."--